Irma Adelman y Cynthia Taft Morris. Economic growth and social equity in developing countries. California : Stanford University Press, 1973. 257 p. - Peña, Raúl de la (Estudios Demográficos y Urbanos, 1974)
IRMA ADELMAN y CYNTHIA TAFT MORRIS, Economic Growth and Social Equity in Developing Countries, California, Stanford University Press, 1973.